Saving, Buying and Spending Patterns of Overseas Filipino Workers in the Ilocos Region - Parilla, Eric S; Abadilla, Marc Edward (International Journal of Entrepreneurship and Sustainability Studies, 2023)
This research study discusses the saving, buying and spending patterns of Overseas Filipino Workers. It used quantitative research design and has 772 OFW-respondents coming from all parts of the country. The sampling design was convenience-snowball non-probability sampling design. Findings suggest that most of the respondents were female, college graduate, have 1-2 dependents and are currently working in Hong Kong. As to buying and spending preferences of OFWs, they intend to plan ahead of time what they are buying. They are responsible spenders since they know how hard it is to earn money abroad. Food, remittance and health and wellness are the major expenses of OFWS. Many OFWs also allot portion of their income to savings. One of the limitations of this study is that this research paper only considered one point in time.